DETECTION AND GENOTYPING OF HCV IN PATIENTS OF SHEIKH ZAYED HOSPITAL, LAHORE, PAKISTAN - Mohammad Tahir; Agha Muhammad Suhail; Fauzia Tahir (Journal of University Medical & Dental College, 1970)
ABSTRACTBACKGROUND: A vast majority of chronically infected HCV individuals remain undiagnosed and unaware of their infection status for several years. This study investigated the prevalence of HCV patients in a tertiary-care hospital.METHODS: Patients attending out-patient department of Sheikh Zayed hospital Lahore were examined during January-March 2012. Diagnosis of Hepatitis C was based on the occurrence of anti-HCV antibodies in serum. HCV RNA infection was conﬁrmed by Real time PCR. Genotypic detection of ampliﬁed product was performed on cytoﬂour. Liver function test (LFT) of ALT was also performed to assess the liver function. RESULTS: Four hundred and ﬁfty four males and 546 females aged 12-80 years were examined for detection and genotyping of HCV. Sixty nine percent of study population belonged to 30-59 yrs, 26% to ≤29 years, and 5% to ≥60 year old age-groups. Fifty ﬁve percent were females. Seventy one percent subjects were found with ALT levels >35. 63% subjects were RNA positive. Forty two percent of males and 58% of females showed genotype 3; In age-groups of ≤19 years, 20-29 years, 30-39 years, 40-49 years, 50-59 years and ≥60 years, genotype 3 was detected in 44%; 51%, 60%, 58%, 58% and 43% respectively. Statistical difference of study variables was nonsigniﬁcant (p≥0214) both for age-groups and genders.CONCLUSION: HCV, genotype 3 highly detected, was equally prevalent in both males and females irrespective of demographic factors. Middle-aged (30-50 years) study population was mostly affected by HCV.